THE RELATIONSHIP BETWEEN FOOD MODIFICATION AND DIETARY PATTERNS WITH NUTRITIONAL STATUS IN TODDLERS - Ernawati Tri Handayani; Siti Maryam; Prisca Dwi Ayu Hartanti (Universitas STRADA Indonesia, 2026)
Lack of appetite is a cause of nutritional problems in toddlers. A child's appetite often changes depending on how parents present the food. Mothers' lack of creativity in food presentation can lead to decreased appetite and unhealthy dietary patterns in children. The aim of this study was to analyze the relationship between food modification and dietary patterns with the nutritional status of toddlers in Tanjungsari Village, Boyolangu Sub-district, Tulungagung Regency. The research design was correlational with a cross-sectional approach. The independent variables were food modification and dietary patterns, and the dependent variable was the nutritional status of toddlers. The research was conducted from October 20th to November 5th, 2025. The study population consisted of all mothers and toddlers at Posyandu I in Tanjungsari Village, Boyolangu Sub-district, Tulungagung Regency, totaling 27 mothers and toddlers aged 7-59 months. The sample was taken using a total sampling technique, consisting of 27 respondents